Health and justice partnerships for young adults – when health and law unite in care. (October 2018) - Ewais, Tatjana; Banks, Cate
Background: Issues of health and law are closely connected in people with chronic illness but as yet there is little emphasis in current health services funding and planning on establishing formal links between these two important areas. Context: The Mater Young Adult Health Centre and Health Advocacy Legal Clinic partnership offers an example of an innovative and effective health–justice and multidisciplinary practice. Health and legal services are co-located in a purpose-built tertiary hospital for adolescents and young adults with complex health needs, which facilitates close collaboration between health and legal professionals and interdisciplinary work. Aim and objectives: In this paper, we explore young people's health and well-being in a contemporary context of holistic care provided within a health–justice partnership in a tertiary hospital for young adults with chronic illness. Methods: Using illustrative examples, we describe the collaborative treatment model involving health and law professionals working in an interdisciplinary clinic. Findings: While we touch on the role of students in the clinic and the educational benefits for the them, our primary focus is on describing the integration of law and health as a model of care and the importance of growth and shift in the understandings of professionals. We provide examples of treatment, coordinated actions and successful outcomes in the well-being of three complex young people, their families and the community. Conclusion: We conclude by offering future visions of service expansion, both in terms of availability on-site as well as increased support.